A Mn-doped Ni2P nanosheet array: an efficient and durable hydrogen evolution reaction electrocatalyst in alkaline media. Issue 80 (25th September 2017) - Zhang, Ya; Liu, Yiwei; Ma, Min; Ren, Xiang; Liu, Zhiang; Du, Gu; Asiri, Abdullah M.; Sun, Xuping
Abstract : A Mn-doped Ni2 P nanosheet array on nickel foam (Mn-Ni2 P/NF) acts as a high-efficiency and durable electrocatalyst for the hydrogen evolution reaction in 1.0 M KOH, driving 20 mA cm −2 at an overpotential of 103 mV, which is 82 mV less than that for Ni2 P/NF. Abstract : Developing earth-abundant and high-performance electrocatalysts toward the alkaline hydrogen evolution reaction (HER) is highly desired. In this communication, we report a Mn-doped Ni2 P nanosheet array on nickel foam (Mn-Ni2 P/NF) as a high-efficiency electrocatalyst for the HER in alkaline solutions. This Mn-Ni2 P/NF can drive 20 mA cm −2 at an overpotential of 103 mV in 1.0 M KOH, which is 82 mV less than that for Ni2 P/NF. In addition, it also demonstrates excellent long-term electrochemical durability for at least 25 h. This work offers us a promising catalyst material for water-splitting devices for large-scale production of hydrogen fuels.